2016
DOI: 10.1103/physrevb.93.041110
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of cyclotron resonance in a two-dimensional electron system

Abstract: It is established that cyclotron resonance (CR) in a high-quality GaAs/AlGaAs two-dimensional electron system (2DES) originates as a pure resonance, that does not hybridize with dimensional magnetoplasma excitations. The magnetoplasma resonances form a fine structure of the CR. The observed fine structure of the CR results from the interplay between coherent radiative and incoherent collisional mechanisms of 2D plasma relaxation. We show that the range of 2DES filling factors from which the phenomenon arises i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…For a fundamental mode with nearly-sinusoidal current distribution one can estimate j 2 ω (r) / j ω (r) 2 = π 2 /8 ∼ 1. The inverse quadratic scaling of radiated power with wavelength is in agreement with recent experimental measurements [49].…”
Section: Absorption Limits By Confined 2d Plasmonssupporting
confidence: 90%
“…For a fundamental mode with nearly-sinusoidal current distribution one can estimate j 2 ω (r) / j ω (r) 2 = π 2 /8 ∼ 1. The inverse quadratic scaling of radiated power with wavelength is in agreement with recent experimental measurements [49].…”
Section: Absorption Limits By Confined 2d Plasmonssupporting
confidence: 90%
“…This is often considered as a hybridization of the plasmon with the cyclotron dispersion [16,17,29]. More recent microwave experiments show that these excitations are coexisting [30,31], but the cyclotron transition remains very hard to observe if nearby the MP resonance due to screening of the incident electric field.…”
Section: Introductionmentioning
confidence: 99%
“…While some photoresistance measurements revealed either only the fundamental [1] or the lowest few odd-order MPR modes [4], another study [6] reported MPR modes with n = 1, 2, 3, 4. Higher order (n 10) MPR have been observed in microwave absorption [14] and spatially resolved photoluminescence [15] and, more recently, even higher modes have been detected in photovoltage [16,17] and differential luminescence spectra [18].…”
mentioning
confidence: 99%
“…At high n, the superradiant rate drops rapidly due to the decay of coherence length L n ∼ w/n [18] and the MPR width is governed by the incoherent rate γ. Therefore, small incoherent scattering rate is another essential ingredient for the detection of high-order MPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation